Implementation of Outcome-Based Education in a Leading High School (a Case Study at SMA Taruna Bakti Bandung) - Varary Mechwafanitiara Cantika; Amsal Alhayat (UM Purwokerto Press, 2023)
Outcome-Based Education (OBE) is an approach to learner-centered learning that prioritizes achieving specific learning outcomes for all students. The approach ensures that students achieve set goals in their learning process. This study aims to determine the implementation of Outcome-Based Education (OBE) at SMA Taruna Bakti Bandung. The research method used is a qualitative case study approach. The results show that SMA Taruna Bakti Bandung prioritizes the cognitive aspects of learning in implementing Outcome-Based Education (OBE). The integration of OBE at SMA Taruna Bakti Bandung is carried out through intracurricular, extracurricular, and special programs. The professionalism of teachers and the availability of facilities and infrastructure support the successful implementation of OBE at SMA Taruna Bakti Bandung. The success of implementing Outcome-Based Education (OBE) at SMA Taruna Bakti Bandung is demonstrated by the achievements of students and graduates. The study concludes that the holistic implementation of Outcome-Based Education (OBE), considering the supporting factors, can encourage the achievement of educational goals. However, it is essential to focus on improving students' cognitive, affective, and psychomotor aspects for mastery of learning.